STRATEGI PENGEMBANGAN PARIWISATA TAMAN KYAI LANGGENG DI KOTA MAGELANG - Atsarina, Atika Indah Nur; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Tourism development of Taman Kyai Langgeng has a goal to increase the visitor's number which resulted in the increasing of local revenues of Magelang City. Taman Kyai Langgeng itself is the main tourist attraction in the Magelang City. This destination currently facing a serious problem due to decreasing number of visitors. The underlying reason why the number keeps falling is the lack of promotion. The aim of this research is to formulate tourism strategy of Taman Kyai Langgeng. This research was conducted at the Taman Kyai Langgeng’s Regional Company of Tourism Object and using the qualitative-descriptive approach. Since there are a lot of interesting tourism destination being established nowadays, Taman Kyai Langgeng needs to be developed in order to maintain its existence. SWOT analysis and Litmus Test are used to find the appropriate strategy. The result indicates four the strategic issues for which the highest scoring strategy is to innovate the game rides. On how to innovate, the research found that the strategy can be applied by utilizing the land and maximalizing capital supports from the Government of Magelang City and investor as well. In addition, enhancing coordination to promote this destination through digital platform is highly required. According to this research, cooperation with the investors should be increased in order to maintain the investigation in Taman Kyai Langgeng. This step is considered as an important step to upgrade the ability of Taman Kyai Langgeng competing with other competitors. Other recommendations that should be implemented by Taman Kyai Langgeng is to update regularly the website and social media contents of this place with the purpose to provide latest information and promotion for both local and international visitors.